Drogodependencia y su efecto en los patrones conductuales de un joven de 24 años de edad del cantón Ventanas - Recalde Naveda, Carlos Vicente (2023)
The present case study was carried out with the objective of identifying through cognitive behavioral therapy techniques to determine if drug dependence influences the behavioral patterns of a 24 year old young man who assists for consultation at the Dr. Jaime Roldós Aguilera basic hospital in the Ventanas canton. Thus, the methodology used in this work is aimed at scientific research of mixed type, where information was collected on the variables: drug dependence and behavioral patterns which are exposed in this case study, also required the use of different techniques of cognitive behavioral therapy, which allowed the objective to be fulfilled optimally to subsequently provide the corresponding therapy to the patient through a therapeutic plan which includes a procedure in an individual therapy aimed at modifying those beliefs that the patient presented during the psychological intervention, all this in order to overcome their problem and improve their quality of life both personally and socially.